Managing the Complex Issues of Pediatric Nonaccidental Trauma: A Simulation-Based Case of a Critically Injured Child - Matthew Ryan; Peggy White; Sean Kiley; Heather Reed; Chris Giordano (Association of American Medical Colleges, 2017)
Introduction Trainees generally have insufficient training in managing critically ill and injured pediatric patients due to limited exposure to such patients. Patient simulation experiences allow trainees to learn management skills needed in such a crisis. Herein, we describe a case regarding a critically injured pediatric patient. This case requires trainees to use teamwork skills, medical knowledge, and technical skills to manage the patient. Methods We developed a team-based simulation regarding the resuscitation of a critically injured child-a toddler with multiple injuries, all requiring emergent care. The case was developed for senior medical students and residents and can be completed in a single 1-hour session, including a debriefing period. We also address psychosocial issues of managing a critically injured child by having the mother and her boyfriend present for part of the case. The team must address the underlying issue of suspected nonaccidental trauma while managing a medical resuscitation. Results We have performed this scenario with a cohort of 100 trainees. Through direct observations, all teams have been able to manage the patient successfully. The average response to the effectiveness of the case in terms of developing pediatric resuscitation skills was very positive, with scores of 6.7 on a scale of 1 to 7. Discussion Medical simulation has been demonstrated to be a valuable tool for assessing the knowledge and skills of trainees. This pediatric simulation improved learners' general understanding of managing a pediatric resuscitation. Accordingly, this case has been incorporated as part of resident and medical student training.